Do BTB ACLR Knees have more MRI signs of PTOA than their Contralateral Normal Knee at 2 Years?. Issue 7 (31st July 2020) - Cantrell, William; Altahawi, Faysal; Li, Xiaojuan; Winalski, Carl; Jones, Morgan; Reinke, Emily; Huston, Laura; Spindler, Kurt; ,
Objectives: The prevalence of patellofemoral joint (PFJ) osteoarthritis (OA) ranges from 8-47% 7-10 years after anterior cruciate ligament reconstructions (ACLR) using bone-patellar tendon-bone (BTB) autograft. In performing BTB ACLR, some hypothesize that either trauma caused by harvest of the patellar bone autograft or altered biomechanics lead to PFJ post traumatic osteoarthritis (PTOA). Our objective was to evaluate by 3T MRI whether the ACLR knees had more signs of early PTOA compared to the contralateral knee within the MOON nested cohort. We hypothesize that a BTB autograft harvested using a minimally traumatic technique will not increase the risk of PFJ OA. Methods: MRIs of operative and contralateral uninjured knees were collected in 60 patients (28 males, mean age 21 years) from a single site in the Multicenter Orthopaedic Outcomes Network (MOON) nested cohort at minimum 2 years post BTB ACLR. Harvesting the patellar block for the BTB autograft was performed using an oscillating saw with a narrow blade, being careful not to extend the cut into the posterior cortex of the patella, and with gentle elevation of the bone block with an osteotome. MRI was performed at 3T (Philips, Achieva) and the imaging protocol included intermediate-weighted sagittal turbo spin-echo (TSE) imaging, axial and coronal fat-saturated TSE imaging, and 3D coronal gradient echo imaging. Structural MRI assessment of the knees was performed using the MRI Osteoarthritis Knee Score (MOAKS) semi-quantitative scoring system by a board-certified musculoskeletal radiologist. The prevalence of cartilage defects in each knee compartment (medial, lateral, patellofemoral), meniscal tears (medial, lateral; yes/no), bone marrow edema-like lesions (BMEL; medial, lateral, patellofemoral; yes/no), effusion (yes/no) and Hoffa synovitis (yes/no) were compared between the reconstructed and contralateral uninjured knees. Hypothesis testing was performed for the PF joint using a logistic regression model where the dependent variable was presence/absence of cartilage loss and the independent variable was knee status (surgical or contralateral). Results: There were no significant differences in the prevalence of cartilage defects (any lesions or full thickness loss) in the PFJ between the surgical BTB ACLR knees and the uninjured non-operative contralateral control knees. 38.3% of BTB ACLR knees had PFJ cartilage defects versus 31.7% of contralateral control knees with PFJ cartilage defects (p>0.05) (Table 1). The BTB ACLR knees had more cartilage defects in the medial and lateral tibiofemoral compartments, more meniscal tears, BMEL, effusion and Hoffa synovitis, than the contralateral knees. Figure 1 shows examples of PFJ cartilage defects on MRI for the reconstructed and contralateral uninjured knees. At 2 years follow-up, KOOS symptoms, sports, pain, and activities of daily living scores were maintained at a high level ranging from 88-98. Conclusion: Although prior studies suggest BTB ACLR increases the risk of PFJ OA, the current study shows no difference in MRI signs of early PTOA in the PFJ. Cartilage defects comparing reconstructed vs. contralateral uninjured knees 2 years after surgery based on MRI were not different. These results should be used in shared decision making with athletes in choosing the appropriate autograft during reconstruction. Future studies will investigate the influence of cartilage defects found in the medial and lateral compartments further.